KINERJA PENGELOLAAN KEUANGAN DAERAH DALAM MENINGKATKAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH KOTA PALEMBANG PROVINSI SUMATERA SELATAN - Krisnawati Arum Kusuma Wardhani (Jurnal Renaissance, 2018)
This research is aimed to find out how the performance of regional financial management of Palembang City in increasing APBD of Palembang City, and how to proportion of revenue and expenditure target of APBD Kota Palembang. The theory used in this study is the concept of performance analysis of regional finances according to Mahmudi (2010), which examines the performance of management of regional keunagan based on the financial performance indicators of regional income and financial performance of Regional Expenditure during the period of 2010 to 2015. In accordance with the focus, Qualitative design, to describe the state of subject / object of research based on facts that appear or as it is (fact finding). Data collection was done by observation, interview, and documentation technique. The result of research shows that the growth of APBD from the side of regional income shows that there is a trend of revenue increase from PAD post, but in general the balancing fund positions still dominate the regional income, so that the high rate of regional dependency is balanced fund. While from the side of regional expenditure, it is envisaged that every year the Local Government of Palembang City always allocates a larger budget to the indirect spending group. This indicates that the Local Government of Palembang City still allocates more budget for things that are not directly related to the implementation of the program such as personnel expenditure in the form of salaries and allowances regulated in law, interest expenditure, grant expenditure, social assistance expenditure, Results to provinces / districts / municipalities and village governments, unexpected financial aid and shopping expenditures.Keywords: Performance, Management, Regional Finance.